Gambaran Iklim Pelayanan Pada Karyawan Rumah Sakit X Di Jakarta Barat - Miranda, Miranda; Omega, Petrayuna Dian (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
Employee perception is a basic part of the service climate. The purpose of this research was to determine the description of the service climate perceived by employees at Hospital X Jakarta Barat. The method used in this research is quantitative descriptive research with research instruments in the form of questionnaire. The questionnaire used is the Service Climate Scale from Scheinder (2002) which has been developed by Carrasco (2012). The questionnaire consisted of 16 statements. Participants in this research were medical employees at the Hospital X Jakarta Barat, which amounted to 118 people. The data analysis used is descriptive statistics. The results of this research indicate that the service climate in Hospital X Jakarta Barat is high by producing an average of 44.12. The implication of this research is that the service climate has an important role in improving employee performance in providing services.